2013
DOI: 10.1021/nn404985h
|View full text |Cite
|
Sign up to set email alerts
|

Using the Plasmon Linewidth To Calculate the Time and Efficiency of Electron Transfer between Gold Nanorods and Graphene

Abstract: We present a quantitative analysis of the electron transfer between single gold nanorods and monolayer graphene under no electrical bias. Using single particle dark-field scattering and photoluminescence spectroscopy to access the homogenous linewidth, we observe broadening of the surface plasmon resonance for gold nanorods on graphene compared to nanorods on a quartz substrate. Because of the absence of spectral plasmon shifts, dielectric interactions between the gold nanorods and graphene are not important a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
201
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(211 citation statements)
references
References 59 publications
8
201
1
1
Order By: Relevance
“…An additional 4-nm-thick dielectric layer with a refractive index n layer = 2.2 was included in the model to account for the surfactants surrounding the chemicallysynthesized AuNRs used in the experiments. 62 The schematic diagrams of the FDTD model with and without a glass substrate as well as additional details are provided in Figures S1 and S4. To approximate total internal reflection excitation, where evanescent waves propagate along the substrate, the k-vector of the simulated excitation was assumed to be parallel to the substrate.…”
Section: Simulationsmentioning
confidence: 99%
“…An additional 4-nm-thick dielectric layer with a refractive index n layer = 2.2 was included in the model to account for the surfactants surrounding the chemicallysynthesized AuNRs used in the experiments. 62 The schematic diagrams of the FDTD model with and without a glass substrate as well as additional details are provided in Figures S1 and S4. To approximate total internal reflection excitation, where evanescent waves propagate along the substrate, the k-vector of the simulated excitation was assumed to be parallel to the substrate.…”
Section: Simulationsmentioning
confidence: 99%
“…For instance, the charge carrier mobility of graphene is reported to be as high as 10 6 cm 2 V -1 s -1 [12]. Thus, when graphene layers are deposited on metallic thin films or functionalized with metallic nanoparticles (e.g., Au or Ag), strong coupling can be induced at the metallic/graphene interface due to the effective charge transfer and this generates a large electric field enhancement at the nanointerface [13][14][15][16][17][18]. The electric field excited on the metallic surface is an evanescent wave and is sensitive towards the refractive-index change of its surrounding media.…”
Section: Introductionmentioning
confidence: 99%
“…The overall efficiency of the device could be enhanced via one or more of the following mechanisms: (1) Photon-LSP scattering, which increases the likelihood of photon absorption by the semiconductor [111,112]; (2) Plasmon-induced resonance energy transfer (PIRET), which occurs between an LSP and the interband transition dipole moment of the semiconductor [113,114]; (3) Hot electron injection generated through the decay of an LSP into an electron-hole pair, a process known as direct electron transfer (DET) [113,[115][116][117][118]. PIRET requires spectral overlap between the LSP emission and the semiconductor absorption [113][114][115], while DET is only available when the hot electron is energetic enough to overcome the Schottky barrier at the interface [113][114][115][116][117][118][119].…”
Section: Energy Transfermentioning
confidence: 99%
“…PIRET requires spectral overlap between the LSP emission and the semiconductor absorption [113][114][115], while DET is only available when the hot electron is energetic enough to overcome the Schottky barrier at the interface [113][114][115][116][117][118][119]. Mechanism (1) is only effective at energies above the band-gap, whereas it has been suggested that mechanism (2) and (3) allow for energy transfer to occur below and above the band-gap energies [113-115, 119, 120], thereby widening the amount of the solar spectrum accessible to the device [7,[120][121][122][123][124][125][126].…”
Section: Energy Transfermentioning
confidence: 99%